ULTRASTRUCTURE CHANGES IN THE RAT BRAIN IN CEREBRAL STROKE - Savosko, S.I.; Chaikovsky, Yu.B.; Makarenko, A.N. (World of Medicine and Biology, 2012)
In article we propose new model of acute stroke that consists in reproducing of chronic occlusion of one general carotid artery and in 10 days of design of intracerebral hematoma in internal capsule of corresponding hemisphere of cerebrum of rats. The comparative analysis of new model with the previously worked out model of acute hemorrhagic stroke showed advantage of the first model in regard to pathogenesis of acute cerebral blood circulation disturbances. The morphological and ultrastructure analysis of brain cortex showed considerable violations in edema and destruction of brain cellular formations.